2018
DOI: 10.4102/curationis.v41i1.1833
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate nursing students’ experience of clinical supervision

Abstract: BackgroundClinical supervision plays a major role in the undergraduate nursing programme. There have been some local studies addressing clinical supervision; however, there still remains a lack of knowledge and understanding how to improve quality supervision of undergraduate nursing students. This article is based on the authors’ original thesis.ObjectivesThe objective of the study was to explore the experiences of undergraduate nursing students on clinical supervision.MethodA descriptive design with a qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 19 publications
(27 reference statements)
2
41
0
8
Order By: Relevance
“…Lack of guidance and supervision may lead to nursing students learning incorrect procedures, become incompetent and lose interest in the nursing profession as they feel frustrated [46]. [15] state that professional nurses are responsible for teaching, supervising, guiding, counselling, assessing and evaluating student nurses in the clinical area. The results of this study revealed that professional nurses in the clinical setting were busy with their administrative roles and patient care but were less supportive of students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of guidance and supervision may lead to nursing students learning incorrect procedures, become incompetent and lose interest in the nursing profession as they feel frustrated [46]. [15] state that professional nurses are responsible for teaching, supervising, guiding, counselling, assessing and evaluating student nurses in the clinical area. The results of this study revealed that professional nurses in the clinical setting were busy with their administrative roles and patient care but were less supportive of students.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing students are evaluated in clinical learning environments where skills and knowledge are applied to patient care [5]. Nonetheless, qualitative ndings from two studies conducted in South Africa and Tanzania demonstrated that students lacked adequate clinical supervision because clinical facilitators were often not available or were spending less time with them in the clinical area [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Other criticisms are that nurses from university degree programmes struggle to "hit the ground running" and require extensive induction processes (12). The graduates from such programmes have also complained of the limited clinical exposure, limited clinical accompaniment during training and the lack of structured practical components in their degree programmes (13). These frustrations have compromised the argument supporting degree-education for nurses resulting in a need for more robust evaluation of universitybased nursing degree programmes especially in resource-limited settings like Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Nursing students are evaluated in clinical learning environments where skills and knowledge are applied to patient care [6]. Nonetheless, qualitative ndings from two studies conducted in South Africa and Tanzania on nursing students experiences of clinical supervision during clinical placement, demonstrated that students lacked adequate clinical supervision because the clinical facilitators were not visiting or spent less amount of time at the facilities to supervise students [17,18].…”
Section: Introductionmentioning
confidence: 99%